Age Is Not a Contraindication for Cartilage Surgery: A Critical Analysis of Standardized Outcomes at Long-term Follow-up. (July 2017) - Filardo, Giuseppe; Andriolo, Luca; Sessa, Andrea; Vannini, Francesca; Ferruzzi, Alberto; Marcacci, Maurilio; Kon, Elizaveta
Background: Age is commonly accepted as a negative prognostic factor in cartilage surgery, and cutoff values of 30 to 40 years have been previously suggested as treatment indication. However, the lower outcome scores documented in older patients do not take in consideration the decreasing requirements of an aging joint. Purpose: To analyze the real effect of age in terms of recovery with respect to the functional level expected for different age categories of patients treated for cartilage lesions. Study Design: Cohort study; Level of evidence, 3. Methods: Patients with International Cartilage Repair Society (ICRS) grade 3-4 defects, involving femoral condyles or trochlea without osteoarthritis, were treated with arthroscopic matrix-assisted autologous chondrocyte transplantation; 157 patients were evaluated with IKDC subjective and Tegner scores before surgery and then after 2 and 10 years. Results were first evaluated by dividing patients into 2 age groups according to the generally approved cutoff value of 40 years. The analysis was then repeated after the scores of each patient were standardized according to the score achievable per the normative data in healthy patients for the corresponding sex and age category. Results: A significant improvement in all scores was observed. IKDC subjective score improved from 38.9 ± 14.5 to 74.7 ± 21.8 at 10 years. When a cutoff value of 40 years was used, older patients reached a significantly worse IKDC subjective value at 10 years (65.8 ± 24.3 vs 77.2 ± 20.4, P = .007). However, different findings were obtained after the scores were standardized. Although optimal results were still found in younger patients (<30 years), patients older than 40 years also appeared to benefit from the treatment, and no significant differences were noted compared with the younger population. Conclusion: The benefit of cartilage treatments in patients with increasing age but without any sign of osteoarthritis was higher than previously reported in literature. In fact, when the decreasing functional level expected by an aging population was considered, standardized results showed an overall benefit after cartilage treatment in patients older than 40 years that was not significantly different from the outcome achieved in younger patients. Thus, age is not a strict contraindication as previously suggested, and future studies should consider standardization of data to prove the real age limit of cartilage treatments.